EVALUATION OF THE COURSE ON FINITE ELEMENT METHOD WITH ANSYS APPLICATION SOFTWARE FOR IMPROVING MECHANICAL ENGINEERING STUDENTS’ PROBLEM-SOLVING SKILLS - Mochammad Agus Choiron; Avita Ayu Permanasari; Nafisah Arina Hidayati (Erudio Journal of Educational Innovation, 2018)
In the previous study, learning process by using relevant software with the course had been developed in the statistic course and mechanical drawing course. This study aimed at investigating the effectiveness of using ANSYS software as a tool to help students fulfil the objectives and competencies of Finite Element Method course. The questionnaire consisting of three simple questions to elicit information about lecturer and course evaluation, level of satisfaction and suggestions for course development. The 60 respondents were taken randomly from two Finite Element course classrooms. The evaluation result showed that 60% students could understand the Finite Element Method lesson better with the assistance of ANSYS, 26% said that there was no significant difference with the previous learning methods, 14 % stated that the method used in the previous learning process was better. Regarding sustaining the use of ANSYS application in the learning process, 89% students agreed to continue since they argued that it could improve their problem-solving skills as essential skills to succeed in the industrial job market.